The first record of Tectusa from the Greater Caucasus, Georgia (Coleoptera: Staphylinidae: Aleocharinae: Oxypodini) - Volker Assing (Contributions to Entomology)
Tectusa abanona spec. nov. (Georgia: Kakheti: Abano pass), the first confirmed record of the oxypodine genus Tectusa Bernhauer, 1899 from the Greater Caucasus, is described and illustrated. The distributions of the two Caucasian representatives of the genus are mapped.